2008
DOI: 10.1002/ajmg.b.30664
|View full text |Cite
|
Sign up to set email alerts
|

The utility of SELENBP1 gene expression as a biomarker for major psychotic disorders: Replication in schizophrenia and extension to bipolar disorder with psychosis

Abstract: While microarray studies are generating novel insights into the etiology of major psychiatric disorders, the validation of microarray-identified candidate genes and their role in the causality of these disorders has been less often studied. We have previously demonstrated, by microarray, up-regulation of SELENBP1 in the brain and blood of patients with schizophrenia. The main aim of the current study was to validate this finding using quantitative real-time PCR (QPCR) in an independent brain cohort that includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 26 publications
5
27
0
1
Order By: Relevance
“…However, Rayman et al [89] have found no evidence to support a positive effect of Se supplementation on mood and quality of life of an elderly population. The gene expression level of selenoprotein binding protein1 has been linked to major psychotic disorders [90]. Our analysis has shown that the GPX1 rs1050450 allele C positively interacts with mental illness and produces a significant association with peroxide induced DNA damage compared to that of the healthy controls both before after Se supplementation.…”
Section: Discussionmentioning
confidence: 82%
“…However, Rayman et al [89] have found no evidence to support a positive effect of Se supplementation on mood and quality of life of an elderly population. The gene expression level of selenoprotein binding protein1 has been linked to major psychotic disorders [90]. Our analysis has shown that the GPX1 rs1050450 allele C positively interacts with mental illness and produces a significant association with peroxide induced DNA damage compared to that of the healthy controls both before after Se supplementation.…”
Section: Discussionmentioning
confidence: 82%
“…Demethylating agents that can reverse the reduced hSP56 expression, consequently recovering the normal balance of HIF-1α and hSP56, may become interesting candidates for future chemopreventive drug development. Understanding the mechanisms by which hSP56 expression is regulated may become useful to understand the functions of hSP56 in other diseases, since SELENBP1 gene expression has been shown to be upregulated in major psychotic disorders such as schizophrenia (26, 27).…”
Section: Resultsmentioning
confidence: 99%
“…22,23 Some of the differentially expressed genes have been proposed to possess pathogenetic relevance. 24,25 Sampling surrogate mononuclear cells allows access to freshly isolated systemic cellular reactivity during a clinically relevant time window among carefully selected homogenous samples of patients. Most studies to date have measured peripheral blood mononuclear cell (PBMC) gene expression levels at baseline or in lymphoblastoid cell lines derived from chronic drug-treated patients, which may not grapple the full potential of this methodology.…”
Section: Introductionmentioning
confidence: 99%